Proses Penegakan Putusan Pengadilan Tata Usaha Negara yang Berkekuatan Hukum Tetap - Mulyana, Momon (PT Elaborium Elevasi Indonesia, 2024)
The aim of this research is to examine and analyze the legal force of State Administrative Court (PTUN) decisions which have permanent legal force, as well as what the sanctions are for State Administrative officials who do not implement these State Administrative Court decisions. The research method used is a normative research method, namely legal research carried out by examining the laws and regulations applied to a particular legal problem. The results of the research are that the decision of the state administrative court is generally binding (erga omnes), so the strength of the decision of the administrative court The state's efforts are the same as the power of statutory regulations. Thus, a state administrative court decision that has permanent legal force has the following powers: 1) binding power; 2) strength of evidence; and 3) executive power. And what are the sanctions for government officials who do not implement state administrative decisions that have permanent legal force (in kracht van gewijsde) according to Article 116 of Law Number 51 of 2009 concerning the Second Amendment to Law Number 5 of 1986 concerning State Administrative Courts, can be subject to penalty.